2021
DOI: 10.3390/molecules26134065
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Biological Evaluation of Novel Pyrazolo[1,2,4]triazolopyrimidine Derivatives as Potential Anticancer Agents

Abstract: Three novel pyrazolo-[4,3-e][1,2,4]triazolopyrimidine derivatives (1, 2, and 3) were designed, synthesized, and evaluated for their in vitro biological activity. All three compounds exhibited different levels of cytotoxicity against cervical and breast cancer cell lines. However, compound 1 showed the best antiproliferative activity against all tested tumor cell lines, including HCC1937 and HeLa cells, which express high levels of wild-type epidermal growth factor receptor (EGFR). Western blot analyses demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…Docking result suggested that thioxanthones TX3 ‐ 6 were active against cancer cells that express EGFR protein. The cancer cells that express EGFR protein were in breast, [25] cervical, [26] lung, [27] and colorectal cancer [28] . Therefore, the synthesized thioxanthones TX3 ‐ 6 were evaluated through the MTT assay against breast (T47D), cervical (HeLa), colorectal (WiDr), and lung (A549) cancer cell lines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Docking result suggested that thioxanthones TX3 ‐ 6 were active against cancer cells that express EGFR protein. The cancer cells that express EGFR protein were in breast, [25] cervical, [26] lung, [27] and colorectal cancer [28] . Therefore, the synthesized thioxanthones TX3 ‐ 6 were evaluated through the MTT assay against breast (T47D), cervical (HeLa), colorectal (WiDr), and lung (A549) cancer cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…[20,21] In many cases, PDGFR protein is often overexpressed in the lung, [18] breast, [22] glioma, [23] and ovarian [24] cancer cell lines. While EGFR protein is expressed in breast, [25] cervical, [26] lung, [27] and colorectal [28] cancer cells. In our previous work on the molecular docking study of thioxanthone derivatives, it was revealed that the important factors influencing their binding energy were the presence of hydroxyl and halogen (i. e., chloro (Cl) and bromo (Br)) substituents.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesized compounds were evaluated for their cytotoxic activity by a photometric rhodamine B assay (SRB) on different human cancer cell lines, malignant melanoma (A375), colon (HT29), breast (MCF-7), human ovarian carcinoma (A2780) and pharynx carcinoma (FaDu); for comparison, non-malignant mouse embryonic fibroblasts (NIH 3T3) and human embryonic kidney cells (HEK293) were included; doxorubicin (DX) was used as a positive control [ 31 , 32 ]. The results are summarized in Table 1 .The EC 50 values in μM from SRB assays were determined after 72 h of treatment, and the values are averaged from three independent experiments performed each in triplicate, confidence interval, CI = 95%; mean ± standard mean error).…”
Section: Resultsmentioning
confidence: 99%
“…Cells were harvested and protein was prepared as described previously (Aliwaini et al 2021). Primary antibodies used for western blotting are anti-p-Stat3 (sc-8059), anti-PARP1/2 (sc-7150), anti-caspase-9 (sc-56076), anti-p53 (sc-126), anti-p21 (sc-756) and anti-α-Tubulin (sc-8035) (Santa Cruz, California, USA).…”
Section: Western Blottingmentioning
confidence: 99%
“…Immunohistochemical analysis revealed that breast cancers that express the estrogen receptor, progesterone receptor or both respond well to hormone therapy (Aliwaini et al 2019;Porras et al 2021). Another important progress in breast cancer therapy was identifying and targeting the Her2 subtype of epidermal growth factor receptors (EGFR) which improved the outcome of Her2positive patients (Aliwaini et al 2021). Triple-negative breast cancers (TNBCs) are called such because they lack receptors for estrogen, progesterone, and Her2.…”
Section: Introductionmentioning
confidence: 99%